"Vibrant Wearables": Material Encounters with the Body as a Soft System. (4th May 2021) - Tsaknaki, Vasiliki; Helms, Karey; Juul Søndergaard, Marie Louise; Ciolfi Felice, Marianela
Abstract: As new materials become available for textile and interaction designers, it is crucial that we develop an understanding of the lived experiences of such materials and explore meaningful contexts for their development. In this paper, we engage with systems in which bodies as materials and materials as bodies constitute an assemblage of vitalities in constant flux with one another. In particular, we address how such systems in their interactions with (non)human bodies blur boundaries between inside and outside the body, and between human and machine, acting as soft systems . Drawing on our first-person, design-led research, we present three design explorations of soft systems that deeply engage with the body: Breathing Wings, Fiddling Necklaces and Menarche Bits. We analyze how the three projects contribute towards what we conceptualize as "vibrant wearables": wearables that through their material vibrancy surface design qualities of leakiness, characterized by a multi-directionality of "spilling over, " ongoingness, which attends to non-linear temporalities and cycles of life and death, and mutuality that emphasizes the interdependency, and becoming, of vibrant encounters. These three design qualities all conceptually trouble boundaries of bodies and materials and are practical resources for designers and researchers working with the body in/as a soft system. Our work offers concrete examples of how to work with material vibrancy, which is particularly relevant to new materialist discourses in textile, fashion and interaction design. We argue for the generativity of these design qualities for other designers and researchers aiming to elevate materials and soft systems in interactions with bodies. Moreover, we contribute towards design research that conceptually and materially troubles the boundaries of the body, and we argue for attending to the material power of (non)human bodies as a soft system.